Resilience and Stress in Later Life: A Network Analysis Approach Depicting Complex Interactions of Resilience Resources and Stress-Related Risk Factors in Older Adults - Thoma, Myriam V.; Höltge, Jan; Eising, Carla M.; Pfluger, Viviane; Rohner, Shauna L. (Frontiers in Behavioral Neuroscience, 2020)
Background: Emerging systemic approaches on resilience propose that a person’s or group’s adaptability to significant stress relies on a network of interdependent resources. However, little knowledge exists on systemic resilience in older survivors of early-life adversity (ELA) and how ELA affects their resource network in later life. Objective: This study investigated how ELA may be linked to the interplay of resources and stress-related risk factors in later life. Research Design and Methods: Data from N=235 older adults (Mage=70.43 years; 46.40% female) were assessed. Half the participants were affected by ELA through compulsory social measures and placements in childhood and/or adolescence (‘risk group’). The other half were age-matched, non-affected participants (‘control group’). Using psychometric instruments, a set of resilience-supporting resources in later life and current stress indices were assessed. Regularized partial correlation networks examined the interplay of resources in both groups, whilst also considering the impact of stress. Results: Both groups demonstrated only positive resource interrelations. Although the control group showed more possible resource connections, the groups did not significantly differ in the overall strength of connections. While group-specific resource interrelations were identified, self-esteem was observed to be the most important resource for the network interconnectedness of both groups. The risk group network showed a higher vulnerability to current stress. Discussion and Implications: Network analysis is a useful approach in the examination of the complex interrelationships between resilience resources and stress-related risk factors in older adulthood.